Polishing of Treated Palm Oil Mill Effluent Using Azolla pinnata (Journal of Biochemistry, Microbiology and Biotechnology, 2022)
Phytoremediation was used in this study to polish treated palm oil mill effluent using Azolla pinnata. The effectiveness of phytoremediation using A. pinnata can be proved through the reduction of the contamination concentration of wastewater before and after treatment. Preliminary study was made to determine the range of variables that are required for Response Surface Methodology (RSM) software. The variables for this study are the quantity of A. pinnata (20-30 grams), the concentration of palm oil mill effluent (60% -10%), and retention time (1-5 days). Characterization of palm oil mill effluent showed the BOD concentration (285 mg/L), and oil and grease (68.1 mg/L) above the emission standards, the Environment Quality Act 1974, (2005). The highest percentage of effectiveness to eliminate contamination after treatment is ammonia nitrate with an average efficiency of 93%. Meanwhile, the process of BOD removal efficiency percentage is the lowest at 46%. The optimization process has been done using the software Design Expert®. Through Variance analysis, the percentage of effectiveness to eliminate the BOD is not significant for the quadratic equation. Optimum conditions for phytoremediation of the palm oil mill effluent using A. pinnata are quantity of A. pinnata (30 g), the concentration of palm oil mill effluent (10%) and retention time (4.7 days) with the reliability or desirability at 0.9. Maximum percentage of effectiveness removal for BOD, COD, TS, TSS, oil and grease, NH3-H and phosphate are 63.67%, 80.02%, 85.89%, 80.58%, 81.50%, 98.44%, 92.92% and 0.90%, respectively.
Keywords: Phytoremediation; green technology; Azolla pinnata; Response Surface Method; optimization